Periodontal treatment need of the 6th-grade Jordanian pupils - A. A. HAMASHA, & Z. ALBASHAIREH (Paediatric Dentistry, 2006)
The purpose of this study was to assess the periodontal treatment needs of 6th-grade Jordanian pupils aged 12 years old.